ParticiPAte CP: A protocol of a randomised waitlist controlled trial of a motivational and behaviour change therapy intervention to increase physical activity through meaningful participation in children with cerebral palsy - Reedman, S.; Boyd, Roslyn; Elliott, Catherine; Sakzewski, L. (BM J Group, 2017)
Introduction: Children with cerebral palsy (CP) participate in leisure-time physical activities (PA) less often, with less intensity and reduced diversity than their typically developing peers. Participation in leisure-time physical activities may be an important source of habitual physical activity (HPA) for children with CP, who as a group have lower levels of HPA and increased sedentary time compared with their typically developing peers. The proposed study aims to compare the efficacy of a participation focused therapy (ParticiPAte CP) to usual care in a pragmatic, randomised waitlist controlled trial. Methods and analysis: Thirty-six children with CP (18 in each group), classified as Gross Motor Function Classification System levels I to III, aged between 8 and 12 years will be recruited across South East Queensland, Australia. Children will be randomised to receive either ParticiPAte CP or waitlist usual care using concealed allocation. ParticiPAte CP is an individually tailored, goal-directed intervention model of pragmatic participation-focused therapy using a toolbox of evidence-based strategies in the treatment of children with CP. This will include goal-setting; identification of barriers and facilitators to participation goals, strategy formation and planning and communication guided by principles of Self-Determination Theory using strategies of Motivational Interviewing. The intervention comprises 8 weekly sessions of 1 hour duration conducted by a physiotherapist in the child's home or community.